Մանիպուլյացիոն մեթոդները կառավարման համակարգում - Քալանթարյան էդգար (YSU Journal of International Affairs, 2016)
Modern public relations are more complicated and have a huge impact on current human interrelationships. Since the very beginning of human society, many have interested in governing the masses and made them oblige to their interests. So there are many mechanisms for that purpose, including the violence, threats, enforcement and etc., at the same time using the ideological impact and charisma. In the modern world, there are more subtle tricks to influence the minds of large social masses, which are not seen and perceived. Manipulation is used almost in all spheres of public life. It should be considered both as a negative and positive phenomenon and a necessary element of the social development process. But mainly, it is carried out in three areas: ideological (propaganda), economic (campaign), and social.